2021
DOI: 10.3390/ijms221810153
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Stromal Cells Alter the Mechanical Stability and Viscoelastic Properties of Gelatine Methacryloyl Hydrogels

Abstract: The extracellular matrix provides mechanical cues to cells within it, not just in terms of stiffness (elasticity) but also time-dependent responses to deformation (viscoelasticity). In this work, we determined the viscoelastic transformation of gelatine methacryloyl (GelMA) hydrogels caused by adipose tissue-derived stromal cells (ASCs) through mathematical modelling. GelMA-ASCs combination is of interest to model stem cell-driven repair and to understand cell-biomaterial interactions in 3D environments. Immor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…The expression of matrix metalloproteases (MMPs), among other enzymes, enable cells to degrade their surrounding environment, facilitating their spreading, migration, or proliferation, among others [ 40 ]. ASCs can alter the stiffness and viscoelasticity of GelMA hydrogels [ 41 ] through elusive mechanisms; however, this might relate to a combination of MMPs’ degradation and matrix deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of matrix metalloproteases (MMPs), among other enzymes, enable cells to degrade their surrounding environment, facilitating their spreading, migration, or proliferation, among others [ 40 ]. ASCs can alter the stiffness and viscoelasticity of GelMA hydrogels [ 41 ] through elusive mechanisms; however, this might relate to a combination of MMPs’ degradation and matrix deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability of the MRC-5 cells cultured on LdECM and Ru-LdECM hydrogels was assessed after 1 and 7 days using Calcein AM (Thermo Scientific, Breda, the Netherlands) to stain live cells and propidium iodide (PI; Sigma-Aldrich) for staining dead cells, as previously described. 30 The hydrogels were first washed with HBSS and then incubated with serum free media containing 5 µM Calcein AM and 2 µM PI, for 1 hour at 37°C. After incubation, fluorescent images were captured using a EVOS Cell Imaging System (Thermo Scientific) with GFP (509 nm) and Texas Red (615 nm) channels.…”
Section: Live/dead Stainingmentioning
confidence: 99%
“…In the field of tissue engineering for regenerative-medicine purposes, Martinez-Garcia and colleagues [8] investigated the combination of gelatine methacryloyl hydrogels and ASCs to model stem cell-driven repair and to understand cell-biomaterial interactions in 3D environments. Indeed, within a 3D environment, stromal cells experience biochemical and biomechanical stimuli, with the extracellular matrix regulating cellular behavior via activation of intracellular signaling pathways and, in response, cells degrade, de-posit, and rearrange matrix components.…”
mentioning
confidence: 99%
“…Indeed, within a 3D environment, stromal cells experience biochemical and biomechanical stimuli, with the extracellular matrix regulating cellular behavior via activation of intracellular signaling pathways and, in response, cells degrade, de-posit, and rearrange matrix components. The authors found that ASCs transform gelatine methacryloyl hydrogel viscoelasticity into a more fluid environment and alter the hydrogel mechanical stability [8]. In addition, out of the concentrations studied, 5% gelatine methacryloyl hydrogel provided the most conducive biomechanical environment for ASCs to spread and remain viable [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation